Gonorrhoea of the sigmoid neovagina in a male-to-female transgender. (July 2015) - van der Sluis, Wouter B; Bouman, Mark-Bram; Gijs, Luk; van Bodegraven, Adriaan A
A 33-year-old male-to-female transgender consulted our outpatient clinic with perneovaginal bleeding during and following coitus. Four years before, she underwent a total laparoscopic sigmoid neovaginoplasty. Physical, histological and endoscopic examination revealed neither focus of active bleeding nor signs of active inflammation. A polymerase chain reaction test performed on a neovaginal swab showed gonococcal infection. Treatment consisted of 500 mg intramuscular ceftriaxone. Three weeks later, our patient reported resolution of symptoms, consistent with eradication of the infection demonstrated by a follow-up neovaginal swab polymerase chain reaction. To our knowledge, this is the first case report of gonococcal infection of the sigmoid neovagina.